Acute mesenteric ischemia: a sequela of abdominal aortography - Shiksha Kedia; Vijaya Raj Bhatt; Ashish Koirala; Srujitha Murukutla; Jharendra Rijal; Shradha Pant; Monika A. Wrzolek; Aaron Gottesman (Greater Baltimore Medical Center, 2014)
The use of abdominal angiography and transcatheter embolization has increased rapidly in the last few decades. Although improvement in angiographic techniques has made the procedure safe, ischemic colitis is a rare but potentially dreadful complication. We report a case of a 51-year-old woman who developed ischemic colitis following aortography, demonstrating that such angiographic studies may produce substantial morbidity.